2021
DOI: 10.1093/plcell/koab236
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptional complex of NGATHA and bHLH transcription factors directs stigma development in Arabidopsis

Abstract: The stigma is an angiosperm-specific tissue that is essential for pollination. In the last two decades, several transcription factors with key roles in stigma development in Arabidopsis thaliana have been identified. However, genetic analyses have thus far been unable to unravel the precise regulatory interactions among these transcription factors or the molecular basis for their selective roles in different spatial and temporal domains. Here, we show that the NGATHA (NGA) and HECATE (HEC) transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Moreover, not only stress-responsive TFs but also many developmental TFs were expressed specifically and extremely differentially in salt-treated CY1000. For instance, BGIOSGA027780 (bHLH), which is similar to HEC3, which is responsible for transmitting tract and stigma development in A rabidopsis , was upregulated 65-fold [ 34 ]. These results indicated that heterosis was caused by the change in the degree of regulation of some genes after crossing between the two parents, resulting in a more sensitive response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, not only stress-responsive TFs but also many developmental TFs were expressed specifically and extremely differentially in salt-treated CY1000. For instance, BGIOSGA027780 (bHLH), which is similar to HEC3, which is responsible for transmitting tract and stigma development in A rabidopsis , was upregulated 65-fold [ 34 ]. These results indicated that heterosis was caused by the change in the degree of regulation of some genes after crossing between the two parents, resulting in a more sensitive response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…After the filtering process, 207 sequences of monocots and dicots were obtained to characterize the gene family (Table S1). The genes were named according to the homology to the Arabidopsis NGA family and the previous literature [6][7][8][9][10][11][12]14,16,18,23].…”
Section: Identification and Characterization Of Nga Genesmentioning
confidence: 99%
“…In Arabidopsis, four NGA genes (AtNGA1, AtNGA2, AtNGA3, AtNGA4) and three NGA-LIKE genes (AtNGA-LIKE1, AtNGA-LIKE2, AtNGA-LIKE3) have been reported [6][7][8][9][10][11][12]. NGA TFs are mainly involved in developing pistils; they are also involved in regulating the shape and size of lateral organs such as leaves and petals and the regulation of seed size [6,8,9,[13][14][15][16][17][18]. Alvarez et al [19] used synthetic miRNAs against A. thaliana NGA genes, showing that single NGA mutants exhibited mild phenotypic changes in lateral organs, while quadruple mutants exhibited defective pistils as well as small, broad leaves with the broad perianth [19].…”
Section: Introductionmentioning
confidence: 99%
“…The basic region, is a DNA-binding region that allows HLH proteins to bind to E-box (CANNTG) ( Massari and Murre, 2000 ). Basic helix-loop-helix transcription factors play crucial roles in plant growth and development including morphogenesis ( Gangappa and Kumar, 2017 ; Ballester et al, 2021 ), iron homeostasis ( Li et al, 2019 ), flower and fruit development ( Sun K. et al, 2019 ), stomatal initiation ( Raissig et al, 2016 ), root vascular cell proliferation ( Ohashi-Ito and Fukuda, 2016 ), grain yield ( Luo et al, 2013 ), secondary metabolites biosynthesis, such as anthocyanin ( Zhao R. et al, 2020 ; Li et al, 2021 ), also in the stress tolerance, for instance, drought ( Verma et al, 2020 ; Zhao Q. et al, 2020 ), salt ( Liu et al, 2021 ; Yu C. et al, 2021 ), cold ( Luo et al, 2020 ; Shen et al, 2021 ), heavy metal toxicity ( Sun W. et al, 2019 ), and osmotic stress ( Yang et al, 2016 ). Despite some bHLHs functions have been elaborated, most plant bHLHs functions are still unclear, especially in tuber crops.…”
Section: Introductionmentioning
confidence: 99%